Optimization of Modified Media & Comparative Production of Citric Acid by Aspergillus niger - Gangavane, Sharad Chandrakant; Upadhye, Vijay Jagdish; Surwase, Babasaheb Shivmurti; Khandagale, Amol Bapurao; More, Vaishnavi Laxmanrao; Shaikh, Shabana Habib (Innovations in Microbiology and Biotechnology Vol. 4, 2022)
To investigate high yield citric acid producers other than citrus fruits, Aspergillus niger was used for submerged citric acid production. Rice and potato extracts were used as substrates in a comparative study to determine which substrate produced the highest yield. The fluctuations in citric acid production yield were traced using varying concentrations of Sucrose, Glucose, and Nitrogen supplements. The concentration of citric acid produced was determined by titration of citric acid extracted from various media. A comparative study was conducted to determine the optimal requirements for increased citric acid production yield. This study can give a better approach for the large-scale industrial production of citric acid as it is among the highly consumed organic acids, by collection of soil sample from Garden of Dayanand Science College, Latur-Maharashtra and isolation of citric acid producing fungi (Aspergillus niger) on PDA medium as pure culture along with cultivation on modified broth medium.